2016
DOI: 10.1111/joic.12310
|View full text |Cite
|
Sign up to set email alerts
|

Real‐World Multicenter Registry of Patients with Severe Coronary Artery Calcification Undergoing Orbital Atherectomy

Abstract: ObjectivesWe evaluated the safety and efficacy of orbital atherectomy in real‐world patients with severe coronary artery calcification (CAC).BackgroundThe presence of severe CAC increases the complexity of percutaneous coronary intervention as it may impede stent delivery and optimal stent expansion. Atherectomy may be an indispensable tool for uncrossable or undilatable lesions by modifying severe CAC. Although the ORBIT I and II trials report that orbital atherectomy was safe and effective for the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…Our multicenter registry reported low rates of angiographic and adverse clinical events in 458 patients with severe CAC who underwent orbital atherectomy followed by stenting . Outcomes of elderly patients who underwent orbital atherectomy have not been previously described.…”
Section: Introductionmentioning
confidence: 92%
“…Our multicenter registry reported low rates of angiographic and adverse clinical events in 458 patients with severe CAC who underwent orbital atherectomy followed by stenting . Outcomes of elderly patients who underwent orbital atherectomy have not been previously described.…”
Section: Introductionmentioning
confidence: 92%
“…While all four patients who experienced dissections were treated successfully with stent deployment, two of the three patients who experienced perforation died. Overall, emergency coronary artery bypass grafting (CABG) was required in only 0.2% of patients in this study . When compared to rotational atherectomy, the frequency of coronary artery dissection and perforation after orbital atherectomy is similar, and are rare events for both procedures .…”
Section: Discussionmentioning
confidence: 80%
“…The ORBIT II Trial reported severe coronary artery dissections in 3.4% of participants (2.3% immediately post‐atherectomy) and coronary artery perforations in 1.8% of participants (0.9% immediately post‐atherectomy) . A retrospective study evaluating the outcomes of orbital atherectomy in 458 patients at three institutions in the United States in a “real world” clinical setting showed a lower incidence of coronary artery perforation (0.7%) and coronary artery dissection (0.9%) . While all four patients who experienced dissections were treated successfully with stent deployment, two of the three patients who experienced perforation died.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, we experienced an unusual and potentially catastrophic complication of atherectomy microtip dislodgement and entrapment in the coronary artery ‐ a “broken arrow” that required meticulous, safe retrieval in order to ensure a favorable clinical outcome. Previously described complications of orbital coronary atherectomy included dissection, perforation, slow flow/no reflow, and abrupt vessel closure . In the ORBIT II trial, these complications were rare with reported incidences of 3.4, 1.8, and 1.8%, respectively , and in the real world experience, complication rates were even lower .…”
Section: Discussionmentioning
confidence: 95%